Chitosan/Alginate Nanogels Containing Multicore Magnetic Nanoparticles for Delivery of Doxorubicin - Sérgio R. S. Veloso; Eva S. Marta; Pedro V. Rodrigues; Cacilda Moura; Carlos O. Amorim; Vítor S. Amaral; Miguel A. Correa-Duarte; Elisabete M. S. Castanheira (MDPI AG, 2023)
In this study, multicore-like iron oxide (Fe3O4) and manganese ferrite (MnFe2O4) nanoparticles were synthesized and combined with nanogels based on chitosan and alginate to obtain a multimodal drug delivery system. The nanoparticles exhibited crystalline structures and displayed sizes of 20 ± 3 nm (Fe3O4) and 11 ± 2 nm (MnFe2O4). The Fe3O4 nanoparticles showed a higher saturation magnetization and heating efficiency compared with the MnFe2O4 nanoparticles. Functionalization with citrate and bovine serum albumin was found to improve the stability and modified surface properties. The nanoparticles were encapsulated in nanogels, and provided high drug encapsulation efficiencies (~70%) using doxorubicin as a model drug. The nanogels exhibited sustained drug release, with enhanced release under near-infrared (NIR) laser irradiation and acidic pH. The nanogels containing BSA-functionalized nanoparticles displayed improved sustained drug release at physiological pH, and the release kinetics followed a diffusion-controlled mechanism. These results demonstrate the potential of synthesized nanoparticles and nanogels for controlled drug delivery, offering opportunities for targeted and on-demand release in biomedical applications.